Creative economy and halal industry for global economic inclusivity in Pekalongan City - Ramadhani, M. Ariel; Hendri Hermawan Adinugraha, (Indonesian Journal of Islamic Economics Research, 2025)
This study investigates how the integration of the creative economy and the halal industry can serve as a strategic mechanism to strengthen global economic inclusivity, with Pekalongan City as the empirical focus. The research aims to analyze the contribution of batik, Muslim fashion, and halal culinary sectors to local identity and economic growth, identify obstacles faced by micro, small, and medium enterprises (MSMEs), and formulate strategies to improve their competitiveness. Using a qualitative descriptive approach, this study adopts a structured literature review of peer-reviewed journal articles, government documents, and relevant international reports to ensure reliable and up-to-date sources. The analysis shows that although the creative sectors hold strong cultural and economic value, MSMEs are constrained by limited digital literacy, inadequate access to inclusive financing, and fragmented halal certification systems. The findings indicate that integrating digital transformation, sharia-compliant financing schemes, and harmonized halal standards can enhance MSME capabilities, expand global market access, and strengthen international recognition. Overall, the study concludes that synergy between the creative economy and the halal industry can build a sustainable ecosystem that promotes innovation and inclusiveness while preserving Pekalongan’s cultural distinctiveness in the global economy.